Comprehensive mutations analyses of FTO (fat mass and obesity-associated gene) and their effects on FTO’s substrate binding implicated in obesity - Kumar, Rakesh; Ningombam, Somorjit Singh; Kumar, Rahul; Goel, Harsh; Gogia, Ajay; Khurana, Sachin; Deo, S. V. S.; Mathur, Sandeep; Tanwar, Pranay (Frontiers in Nutrition, 2022)
An excessive amount of fat deposition in the body leads to obesity which is a complex disease and poses a generic threat to human health. It increases the risk of various other diseases like diabetes, cardiovascular disease, and multiple types of cancer. Genomic studies have shown that the expression of fat mass obesity (FTO) gene was highly altered and identified as one of the key biomarkers for obesity. Present study has been undertaken to investigate the mutational profile of FTO gene and elucidated their effect on protein structure and function. Harmful effects of various missense mutations were predicted using different independent tools and observed that all mutations were highly pathogenic. Molecular dynamics (MD) simulations were performed to study the structure and function of FTO protein upon different mutations and found that mutations decreased the structure stability and affected protein conformation. Furthermore, protein residue network analysis suggested that mutations affected the overall residues bonding and topology. Finally, molecular docking coupled with MD simulation suggested that mutations affected FTO substrate binding by changing the protein-ligand affinity. Hence, the results of current finding would help in depth understanding of the molecular biology of FTO gene and their variants and lead to the development of effective therapeutics against associated disease and disorders.